КОРЕКЦІЯ ПОХИБОК У ПРИЛАДАХ ДЛЯ ВИМІРЮВАННЯ ПАРАМЕТРІВ ЕЛЕКТРИЧНОЇ ЕНЕРГІЇ - Карасінскій, О.Л.; Тесик, Ю.Ф. (Інститут електродинаміки НАН України, Київ, 2021)
A study of methods for correcting amplitude and phase errors in devices for measuring the parameters of electric power with digital signal processing with a sampling frequency multiple of the network frequency was made. The generalized flow diagram of measuring device that consists of a few entrance channels was presented. Mathematical expositions that explain the process of correction of additive and multiplicative errors are given. Through a temporal diagram a few variants of encoding of entrance signals are shown. The possibility of correcting phase errors by shifting the moment of the ADC start-up and by turning the axes and transforming the coordinates of the voltage and current vectors is shown. The possibility of correction when measuring the reactive and reactive powers is investigated. Referencese 10, table 1, figures 5.